Zaufanie interpersonalne jako komponent relacji edukacyjnych i pomocowych - Piorunek, Magdalena (Studia Edukacyjne, 2018)
The category of trust has been considered in numerous philosophical, sociological, psychological, economic, legal, and educational deliberations. The issue of whether trust occurs in or is absent from human relationships has been widely discussed in the social discourse and has been a component of social capital of organisations.This paper reviews interdisciplinary literature to characterise and describe the phenomenon, identifying its dimensions, types, and patterns. It focuses on interpersonal trust as a factor characterising the functioning in organisations, also with reference to educational institutions. The author also identifiestrust in the context of helping relationships in which it is a component of the contractforming process between those who provide and those who use help, of establishing and developing relationships.